Song of the lion - Hillerman, Anne, 1949- (Hillerman, Tony, Leaphorn and Chee novel., 2017)
A deadly bombing takes Navajo Tribal cops Bernadette Manuelito, Jim Chee, and their mentor, the legendary Lieutenant Joe Leaphorn, back into the past to find a vengeful killer in this riveting Southwestern mystery. When a car bomb kills a young man in the Shiprock High School parking lot, Officer Bernadette Manuelito discovers that the intended victim was a mediator for a multi-million-dollar development planned at the Grand Canyon. But what seems like an act of ecoterrorism turns out to be something far more nefarious and complex. Piecing together the clues, Bernadette and her husband, Sergeant Jim Chee, uncover a scheme to disrupt the negotiations and inflame tensions between the Hopi and Dine tribes. Retired Lieutenant Joe Leaphorn has seen just about everything in his long career. As the tribal police<U+2019>s investigation unfolds, he begins to suspect that the bombing may be linked to a cold case he handled years ago. As he, Bernadette, and Chee carefully pull away the layers behind the crime, they make a disturbing discovery: a meticulous and very patient killer with a long-simmering plan of revenge.